2013
DOI: 10.1103/physrevlett.110.237601
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Multiferroic HexagonalLuFeO3Films

Abstract: The crystal and magnetic structures of single-crystalline hexagonal LuFeO(3) films have been studied using x-ray, electron, and neutron diffraction methods. The polar structure of these films are found to persist up to 1050 K; and the switchability of the polar behavior is observed at room temperature, indicating ferroelectricity. An antiferromagnetic order was shown to occur below 440 K, followed by a spin reorientation resulting in a weak ferromagnetic order below 130 K. This observation of coexisting multip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
174
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(184 citation statements)
references
References 31 publications
8
174
2
Order By: Relevance
“…As both (100) and (101) reflections were observed at low temperature, the resolution-corrected integrated intensities were refined using a two-representation model with basis vectors of both the A 1 and A 2 representations, thereby allowing for rotation of the moments in the plane while requiring only two free parameters after scaling to the integrated intensities of several nuclear reflections. At 5 K the moments are found to be coherently rotated in the a-b plane 25 (5) • from the pure A 2 configuration toward the A 1 with m = 3.55 (9) could not be determined here and was thus fixed to zero in these refinements; this is consistent with a ferromagnetic moment less than 0.1μ B /Fe based upon recent studies of thin films [13][14][15][16], whose intensity is further suppressed by the structure factor for the special position of the transition metal species.…”
Section: A Lufe 1−x Mn X Osupporting
confidence: 57%
See 1 more Smart Citation
“…As both (100) and (101) reflections were observed at low temperature, the resolution-corrected integrated intensities were refined using a two-representation model with basis vectors of both the A 1 and A 2 representations, thereby allowing for rotation of the moments in the plane while requiring only two free parameters after scaling to the integrated intensities of several nuclear reflections. At 5 K the moments are found to be coherently rotated in the a-b plane 25 (5) • from the pure A 2 configuration toward the A 1 with m = 3.55 (9) could not be determined here and was thus fixed to zero in these refinements; this is consistent with a ferromagnetic moment less than 0.1μ B /Fe based upon recent studies of thin films [13][14][15][16], whose intensity is further suppressed by the structure factor for the special position of the transition metal species.…”
Section: A Lufe 1−x Mn X Osupporting
confidence: 57%
“…Recent ab initio calculations [12] have suggested that the closely related family of hexagonal ferrites such as LuFeO 3 (h-LFO) may exhibit greatly enhanced magnetic properties relative to their manganite counterparts due to enhanced exchange interactions, larger localized magnetic moments, and differences in the local electronic anisotropy between Mn 3+ and Fe 3+ . In fact, recent investigations of thin films of h-LFO demonstrate that magnetic order occurs as high as 150 K with the simultaneous appearance of a net ferromagnetic (FM) moment parallel to the ferroelectric axis [13][14][15][16] consistent with ab initio calculations [12]. To date, studies of this material have been limited to thin films as h-LuFeO 3 is metastable in bulk and instead forms the centrosymmetric and nonpolar orthorhombic Pbnm structure, precluding ferroelectricity [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study on hLuFeO 3 , strong exchange coupling leading to high magnetic transition temperatures and spin re-orientation transitions closely connected with structural distortions have been identified [16]. Thin films of hLuFeO 3 have shown evidence for a room temperature multiferroic [17] and has been identified as a strong candidate for linear magnetoelectric coupling and control of the ferromagnetic moment directly by an electric field [18]. However, bulk LuFeO 3 normally crystallizes in orthorhombic P bnm symmetry thereby precluding the possibility of ferroelectricity.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Using epitaxial stabilization, however, it is possible to make a metastable hexagonal polymorph of LuFeO 3 that is isostructural with YMnO 3 and other hexagonal rare-earth manganites. 21 In this hexagonal structure, LuFeO 3 has been measured to be both ferroelectric 22,23 and weakly ferromagnetic, [22][23][24] with first principles calculations predicting the ability to reverse the magnetization with a change in polarization. 25 It was recently reported that h-LuFeO 3 is antiferromagnetically ordered at room temperature with a canted antiferromagnetic ordering at T N = 130 K, 23 making it one of the few known room-temperature multiferroics (in this work we will refer to the onset of canted antiferromagnetic order, which is what we can measure, as the Néel temperature).…”
mentioning
confidence: 99%